Biochars from Olive Stones as Carbonaceous Support in Pt/TiO2-Carbon Photocatalysts and Application in Hydrogen Production from Aqueous Glycerol Photoreforming - Juan Carlos Escamilla-Mejía; Jesús Hidalgo-Carrillo; Juan Martín-Gómez; Francisco J. López-Tenllado; Rafael Estévez; Alberto Marinas; Francisco J. Urbano (Nanomaterials, 2023)
Several biochars were synthesized from olive stones and used as supports for TiO2, as an active semiconductor, and Pt as a co-catalyst (Pt/TiO2-PyCF and Pt/TiO2-AC). A third carbon-supported photocatalyst was prepared from commercial mesoporous carbon (Pt/TiO2-MCF). Moreover, a Pt/TiO2 solid based on Evonik P25 was used as a reference. The biochars used as supports transferred, to a large extent, their physical and chemical properties to the final photocatalysts. The synthesized catalysts were tested for hydrogen production from aqueous glycerol photoreforming. The results indicated that a mesoporous nature and small particle size of the photocatalyst lead to better H2 production. The analysis of the operational reaction conditions revealed that the H2 evolution rate was not proportional to the mass of the photocatalyst used, since, at high photocatalyst loading, the hydrogen production decreased because of the light scattering and reflection phenomena that caused a reduction in the light penetration depth. When expressed per gram of TiO2, the activity of Pt/TiO2-PyCF is almost 4-times higher than that of Pt/TiO2 (1079 and 273 mmol H2/gTiO2, respectively), which points to the positive effect of an adequate dispersion of a TiO2 phase on a carbonaceous support, forming a highly dispersed and homogeneously distributed titanium dioxide phase. Throughout a 12 h reaction period, the H2 production rate progressively decreases, while the CO2 production rate increases continuously. This behavior is compatible with an initial period when glycerol dehydrogenation to glyceraldehyde and/or dihydroxyacetone and hydrogen predominates, followed by a period in which comparatively slower C-C cleavage reactions begin to occur, thus generating both H2 and CO2.